Performance Assessment of Single Flash PLTP LMB 1 After First Year Inspection Using ASME PTC 46:1996 Method - Joni Welman Simatupang; Asep Mamat Rahmat Solihat (Fakultas Teknik, 2023)
PLTP LMB 1 performs a First-Year Inspection after operating for one year to inspect and repair equipment after the operation. After these activities, a performance test needs to be carried out to determine the effectiveness and success of these activities. ASME PTC 46: 1996 is a widely-used standard for analyzing the performance test of thermal power plant systems, which includes plant heat rate, power output, specific mass consumption, and more. The purpose of the testing is to evaluate the results of system improvements. Calculation and comparative analysis are performed to determine the system's condition during warranty, commissioning, and testing, as well as after one year of operation and post-first year inspection. After testing, the thermal performance of PLTP LMB 1 was obtained as follows: The corrected net plant heat rate (NPRH) was 18923 kJ/kWh, the corrected net power output was 56,417 MW, and the net specific mass consumption (NSMC) was 6,881 tons/MW. Based on the data guarantee, the thermal performance value of PLTP LMB1 is still below the required value, so it can be concluded that the thermal performance value of PLTP LMB1 is in good condition. The isentropic turbine efficiency value decreased by 2.1% from its design value of 85% to 82.9%, which was caused by suboptimal heat energy absorption by the turbine above the design pressure of 5 bar.